Absence of LPA1 signaling results in defective cortical development - Estivill-Torrús, Guillermo; Llebrez Zayas, Pedro; Matas-Rico, Elisa; Rodriguez-de-Fonseca, Fernando; Chun, Jerold; Santín-Núñez, Luis Javier; Pedraza-Benítez, María del Carmen; De-Diego-Barbado, Isabel; Del Arco-Herrera, Ignacio; Fernández-Llebrez, Pedro (Oxford academy, 2008)
Lysophosphatidic acid (LPA) is a simple phospholipid with extracellular signaling properties mediated by specific G protein-coupled receptors. At least 2 LPA receptors, LPA(1) and LPA(2), are expressed in the developing brain, the former enriched in the neurogenic ventricular zone (VZ), suggesting a normal role in neurogenesis. Despite numerous studies reporting the effects of exogenous LPA using in vitro neural models, the first LPA(1) loss-of-function mutants reported did not show gross cerebral cortical defects in the 50% that survived perinatal demise. Here, we report a role for LPA(1) in cortical neural precursors resulting from analysis of a variant of a previously characterized LPA(1)-null mutant that arose spontaneously during colony expansion. These LPA(1)-null mice, termed maLPA(1), exhibit almost complete perinatal viability and show a reduced VZ, altered neuronal markers, and increased cortical cell death that results in a loss of cortical layer cellularity in adults. These data support LPA(1) function in normal cortical development and suggest that the presence of genetic modifiers of LPA(1) influences cerebral cortical development.
Keywords: Cerebro - Evolución; brain development; cerebral cortex; LPA; lysophosphatidic acid; neurogenesis